Implementation of Contextual Teaching and Learning Model on Web-Based Learning Multimedia for Database Subjects - Dini, Nur Amruna; Prabawa, Harsa Wara; Erlangga, Erlangga (Jurnal Guru Komputer, 2021)
Database is one of the important components in an information system because the database will provide information that will be used by the user. Preliminary research reveals information that understanding material regarding Entity Relationship Diagram (ERD) is still difficult for students to understand. Understanding database concepts requires relationships that are based on perceptions in the real world. Contextual Teaching and Learning (CTL) is a learning concept that will help teachers to relate learning material to the actual situation experienced by students. This research uses comparative causal quantitative research and applies the Extensive Lifecycle (ELC) software development method. This research got the following results: 1) Multimedia web-based learning has a percentage of 188.5 with the category "Very Good" by media experts. 2) The use of web-based learning multimedia with the CTL model has been proven to improve students' conceptual understanding as evidenced by an increase in the mean gain value of 0.59 with the effectiveness criterion of "moderate". 3) Based on the correlation test, there is a relationship between student gain scores and multimedia learning. 4) Students provide an assessment of multimedia learning by giving a score of 312 from the ideal score of 334.